(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article provides information about the damage caused by terrorist organizations to society operating under the guise of religion, the poisoning of the human mind, in particular young people, with the help of social networks. Also, it talks about the methods and techniques used by recruiters.